The Implementation of AHP and Whale Optimization Algorithm In The Selection and Optimization of Best Clean Energy Source - Simorangkir, Niklas Parlindungan; Pratama, Aditya Tirta (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
Clean energy sources have become more and more important in the present time, especially with the goal to reduce the production of greenhouse gases. There are various clean energy sources available, and care must also be taken into which clean energy source is more prevalent in which location. Furthermore, with the multiple alternatives for such clean sources, a method has to be developed to choose the best one, and, if possible, have it optimized to produce the best performance. It is also good if the method developed only requires theories without any need of practical applications in real life (although this is strongly encouraged). This paper will show the utilization of a decision-making tool, namely the analytic hierarchy process, to decide the best energy source and which components are important and then conducts the optimization process through whale optimization algorithm. The research will then conclude with the best energy source chosen in its optimized state. It is hoped that this research will open a gateway into determining which energy sources to use digitally without any recourse to incurring costs on its way.